Integrated Computer-Aided Design in Automotive Development Development Processes, Geometric Fundamentals, Methods of CAD, Knowledge-Based Engineering Data Management - Mario, Hirz.; Dietrich, Wilhelm; Gfrerrer, Anton; Lang, Johann; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The automotive industry faces constant pressure to reduce development costs and time while still increasing vehicle quality. To meet this challenge, engineers and researchers in both science and industry are developing effective strategies and flexible tools by enhancing and further integrating powerful, computer-aided design technology. This book provides a valuable overview of the development tools and methods of today and tomorrow. It is targeted not only towards professional project and design engineers, but also to students and to anyone who is interested in state-of-the-art computer-aided development. The book begins with an overview of automotive development processes and the principles of virtual product development. Focusing on computer-aided design, a comprehensive outline of the fundamentals of geometry representation provides a deeper insight into the mathematical techniques used to describe and model geometrical elements. The book then explores the link between the demands of integrated design processes and efficient data management. Within automotive development, the management of knowledge and engineering data plays a crucial role. Some selected representative applications provide insight into the complex interactions between computer-aided design, knowledge-based engineering and data management and highlight some of the important methods currently emerging in the field.
Automotive Development Processes -- Geometric Fundamentals -- Modeling Techniques in CAD -- Knowledge-Based Design -- Engineering Data Management -- Knowledge Management in Product Development -- Knowledge-Based Engineering Data Management -- Advanced Applications of CAD/EDM in the Automotive Industry.
Keywords: Engineering; Computer-aided engineering; Engineering design; Automotive engineering; Quality control; Reliability; Industrial safety; Engineering; Engineering Design; Computer-Aided Engineering (CAD, CAE) and Design; Automotive Engineering; Quality Control, Reliability, Safety and Risk